2019
DOI: 10.1080/15592294.2019.1625672
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation patterns in human iPSC-derived sensory neuronal differentiation

Abstract: Sensory neurons of the peripheral nervous system are critical in health and disease. Sensory neurons derived from induced pluripotent stem (iPS) cells are now being used increasingly for in vitro models of neuropathy, pain, and neurotoxicity. DNA methylation is critical for neurodevelopment and has been implicated in many neuronal diseases, but has not been examined in iPS-derived sensory neurons. In order to better characterize the iPS-derived sensory neuron model, we have undertaken a genome-wide DNA methyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
(32 reference statements)
0
10
0
Order By: Relevance
“…The use of iPSCs can overcome the ethical issues of ESCs and is considered as a promising alternative for drug screening, disease modeling, and development of clinical treatments [27][28][29]. The molecular [8,11,30,31]. In our previous study, we reported that METTL1-deficient mouse ESCs display defective self-renewal and neural differentiation [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of iPSCs can overcome the ethical issues of ESCs and is considered as a promising alternative for drug screening, disease modeling, and development of clinical treatments [27][28][29]. The molecular [8,11,30,31]. In our previous study, we reported that METTL1-deficient mouse ESCs display defective self-renewal and neural differentiation [13].…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanisms underlying self-renewal and maintenance of pluripotency in iPSCs have been extensively studied. The stem cell genome undergoes reversible epigenetic modifications that regulate gene expression and dictate cell development and differentiation [ 8 , 11 , 30 , 31 ]. In our previous study, we reported that METTL1-deficient mouse ESCs display defective self-renewal and neural differentiation [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, cell reprograming has been suggested to induce epigenetic changes, which constitute another important bias in pain studies (Thanuthanakhun et al, 2021). Specifically, differentiation has been shown to reduce DNA methylation (Ankam et al, 2019;Efrat, 2020). Our current inability to distinguish between differentiationinduced epigenetic modifications and the donor epigenome suggests that caution is needed in interpreting results of subject-specific iPSC-derived models.…”
Section: Differentiation-inducedmentioning
confidence: 97%
“…Recent research allows the obtention of sensory neurons of human through the differentiation of induced pluripotent stem cells (iPS). [31][32][33][34][35][36][37][38] Hence, after validation of the model by induction of SP release we were interested in the expression of ZIKV entry receptors in keratinocytes and in human sensory nerve endings that are in the first line of external environment.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…The limitation of these models is that sensory neurons were issued from animals. Recent research allows the obtention of sensory neurons of human through the differentiation of induced pluripotent stem cells (iPS) 31–38 …”
Section: Introductionmentioning
confidence: 99%